Imputation in genome-wide association analysis - Marchini, Jonathan (Henry Stewart Talks, 2017)
The general problem of imputation, Testing imputed SNPs for association, Examples of imputation in the WTCCC, Properties of imputation (LD, populations, chips, allele frequency), Using imputed data for meta-analysis, The Strand Issue and Imputation QC metrics, The 1000 Genomes Project, Pre-phasing and haplotype estimation, The Haplotype Reference Consortium